Poly-l-lysine-coated magnetic nanoparticles as intracellular actuators for neural guidance - Riggio C; Calatayud MP; Hoskins C; Pinkernelle J; Sanz B; Torres TE; Ibarra MR; Wang L; Keilhoff G; Goya GF; Raffa V; Cuschieri A (International Journal of Nanomedicine, 2012)
Cristina Riggio,1,* Maria Pilar Calatayud,2,* Clare Hoskins,3 Josephine Pinkernelle,4 Beatriz Sanz,2 Teobaldo Enrique Torres,2,5 Manuel Ricardo Ibarra,2,5 Lijun Wang,3 Gerburg Keilhoff,4 Gerardo Fabian Goya,2,5 Vittoria Raffa,1,6 Alfred Cuschieri1,3 1Institute of Life Science, Scuola Superiore Sant’Anna, Piazza Martiri della Libertà, Pisa, Italy; 2Instituto de Nanociencia de Aragón, Universidad de Zaragoza. Mariano Esquillor, Zaragoza, Spain; 3IMSaT, Institute for Medical Science and Technology, University of Dundee, Dundee, Scotland; 4Otto-von-Guericke University, Institute of Biochemistry and Cell Biology, Magdeburg, Germany; 5Departamento de Física de la Materia Condensada, Facultad de Ciencias, Universidad de Zaragoza. Cerbuna 12, Zaragoza, Spain; 6Department of Biology, Università di Pisa, Pisa, Italy*These authors contributed equally to this workPurpose: It has been proposed in the literature that Fe3O4 magnetic nanoparticles (MNPs) could be exploited to enhance or accelerate nerve regeneration and to provide guidance for regenerating axons. MNPs could create mechanical tension that stimulates the growth and elongation of axons. Particles suitable for this purpose should possess (1) high saturation magnetization, (2) a negligible cytotoxic profile, and (3) a high capacity to magnetize mammalian cells. Unfortunately, the materials currently available on the market do not satisfy these criteria; therefore, this work attempts to overcome these deficiencies.Methods: Magnetite particles were synthesized by an oxidative hydrolysis method and characterized based on their external morphology and size distribution (high-resolution transmission electron microscopy [HR-TEM]) as well as their colloidal (Z potential) and magnetic properties (Superconducting QUantum Interference Devices [SQUID]). Cell viability was assessed via Trypan blue dye exclusion assay, cell doubling time, and MTT cell proliferation assay and reactive oxygen species production. Particle uptake was monitored via Prussian blue staining, intracellular iron content quantification via a ferrozine-based assay, and direct visualization by dual-beam (focused ion beam/scanning electron microscopy [FIB/SEM]) analysis. Experiments were performed on human neuroblastoma SH-SY5Y cell line and primary Schwann cell cultures of the peripheral nervous system.Results: This paper reports on the synthesis and characterization of polymer-coated magnetic Fe3O4 nanoparticles with an average diameter of 73 ± 6 nm that are designed as magnetic actuators for neural guidance. The cells were able to incorporate quantities of iron up to 2 pg/cell. The intracellular distribution of MNPs obtained by optical and electronic microscopy showed large structures of MNPs crossing the cell membrane into the cytoplasm, thus rendering them suitable for magnetic manipulation by external magnetic fields. Specifically, migration experiments under external magnetic fields confirmed that these MNPs can effectively actuate the cells, thus inducing measurable migration towards predefined directions more effectively than commercial nanoparticles (fluidMAG-ARA supplied by Chemicell). There were no observable toxic effects from MNPs on cell viability for working concentrations of 10 µg/mL (EC25 of 20.8 µg/mL, compared to 12 µg/mL in fluidMAG-ARA). Cell proliferation assays performed with primary cell cultures of the peripheral nervous system confirmed moderate cytotoxicity (EC25 of 10.35 µg/mL).Conclusion: These results indicate that loading neural cells with the proposed MNPs is likely to be an effective strategy for promoting non-invasive neural regeneration through cell magnetic actuation.Keywords: magnetic nanoparticle, actuator, migration, neural regeneration